Tinjauan Yuridis Terhadap Tindak Pidana Bullying Di Sekolah - Valentina Pinky Kristinawati; Edi Pranoto (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Schools should be a comfortable and safe place for students who are educated in them, but do not rule out that there are several incidents or cases that could endanger the safety of the students themselves, namely bullying at school. Bullying itself can be interpreted as a form of oppression or violence that is carried out intentionally by one person or group of people who are stronger or more powerful towards other people, with the aim of hurting and doing it continuously. Thus it is necessary to conduct research on this matter related to legal protection. This study uses a normative juridical method, which is a method based on legal material that examines theories, concepts, legal principles, and laws and regulations related to the theme of this research. The objectives to be achieved by the author in this study are: 1). Responding to forms of bullying in schools 2). Legal protection for victims of bullying at school. The results of this study produce data that forms of bullying can be categorized into three, namely physical bullying, verbal, and cyberbullying. Meanwhile, legal protection that can be carried out for victims is preventive and repressive with the help of several parties to prevent or overcome bullying in schools.